THE PRIMACY OF SOCIAL NETWORKS IN ENTREPRENEURSHIP: A STUDY OF NETWORKING ABILITY AND INNOVATIVENESS AMONG UNIVERSITY STUDENTS IN NORTH CENTRAL NIGERIA - Abu Amodu, AMEH; Aka, Ama (PEOPLE: International Journal of Social Sciences, 2017)
The study; The Primacy of Social Networks in Entrepreneurship: A Study of Social Networking Ability and Innovativeness among University Students in North Central Nigeria, ascertained the relationship between networking ability and innovativeness. To achieve this, a correlational survey of 402 respondents being the students of the five selected universities was conducted. The study used primary data that were generated using structured questionnaires that were administered on the selected respondents. Descriptive statistics, correlation and other diagnostics were used to analyse the data and to test the hypothesis. The study found a strong correlation between networking ability and innovativeness (r=0.336, p{0.05, n=402). Based on the findings of the study, it was recommended that students’ networking ability should be encouraged by the universities, governments, patrons, role models and policy makers, especially now that there is an increased need for entrepreneurship the world over in the quest to curb youth unemployment. It is also suggested that networking ability and activities should be incorporated into the curricular of higher institutions as it has been discovered to facilitate innovativeness among members of NASE (Network of African Student Entrepreneurs).